Determinants of Financial Reporting Quality Mediated in the Prevention of Fraudulent Financial Reporting and Firm Size as a Moderator - Ade Onny Siagian; Adler Haymans Manurung; Tri Widyastuti; Wastam Wahyu Hidayat (Annals of Human Resource Management Research, 2026)
Purpose: This study examines the effects of good corporate governance, internal audit function effectiveness, organizational culture, and information technology innovation on the quality of financial reporting, with the prevention of fraudulent financial reporting as a mediator. Additionally, it investigates the role of firm size as a moderating variable. Research Methodology: A survey method was used to gather data from the finance director/general manager, audit committee, internal audit unit manager (SPI), and accounting manager/finance manager at a state-owned enterprise (BUMN). Data analysis was conducted using a Structural Equation Model (SEM) with a Partial Least Squares (PLS) approach. Results: This study found that good corporate governance, internal audit effectiveness, organizational culture, and information technology innovation positively affect the prevention of fraudulent financial reporting. Good corporate governance, organizational culture, and IT innovation also improve financial reporting quality. However, internal audit effectiveness does not directly impact financial reporting quality. Firm size strengthens the positive relationship between governance mechanisms and financial reporting quality, both directly and through fraudulent financial reporting prevention. Conclusions: This study concludes that good corporate governance, internal audit effectiveness, organizational culture, and IT innovation are critical for enhancing financial reporting quality and preventing fraud. Firm size moderates the relationship, thereby amplifying the impact of these factors. Limitations: This study is limited to state-owned enterprises (BUMNs) and relies on self-reported data, which may introduce bias. Contributions: This research contributes insights into improving financial reporting practices by highlighting the roles of governance and organizational factors.